Sostenibilidad ambiental del cultivo de café (Coffea arabica) en el Ecuador - Mosquera Kontong, Derian Marlon (2024)
This document deals with the environmental sustainability of coffee cultivation (Coffea arabica) in Ecuador. The objectives set were to detail the environmental impact generated by the management of coffee cultivation and to establish the importance of the environmental sustainability of coffee cultivation. Information was collected from current texts, articles, magazines, talks, conferences, online libraries and scientific bibliographic material that contributed to the creation of the document. The conclusions detail that Ecuadorian climatic conditions are conducive to coffee production, representing an important good within the country's agricultural production, the coffee system is adjusted to establish a tacit commitment to the environment by reducing the use of agrochemicals and preserving the integrity of the soil, which makes it possible to increase production rates and competitiveness in the coffee sector, through the synergistic interaction between the different interested groups, the future of coffee production is closely linked to the well-being of the environment. Both robusta and arabica coffee are produced in Ecuador. Coffee is a prominent crop in the country, involving approximately 50,000 families, composed predominantly of small producers who use agroforestry production systems. On the environmental side, coffee is predominantly grown within agroforestry systems and serves to help in the preservation of natural resources and biodiversity and the establishment of coffee plantations can also be seen as part of the initiatives aimed at safeguarding natural resources.